Gases in sea ice - Tison, Jean-Louis; Delille, Bruno; Papadimitriou, Stathys (2016)
The multiphase dynamics of gases in sea ice is controlled by the physics of the system (initial incorporation, concentration/dilution, transport), internal biogeochemical reactions (biological activity, CaCO3-brine equilibrium in the case of carbon dioxide), and exchange with the atmosphere and the underlying ocean. The thermodynamic equilibrium between the gaseous phase (bubbles) and the liquid phase (gas dissolved in brine) of gases also influences their phase distribution and internal transport along the temperature and salinity gradients in sea ice, as well as gas transport across the ice-water and ice-air interfaces. Here, existing information is presented and discussed on the distribution and flux of the major atmospheric gases, nitrogen, oxygen, and argon, potent climate gases (carbon dioxide, methane, nitrous oxide, dimethyl sulphide), and halocarbons in sea ice. SCOPUS: ch.b info:eu-repo/semantics/published